Creating capsules with cubanes. Issue 29 (4th July 2018) - Kusumoto, Sotaro; Kobayashi, Fumiya; Ohtani, Ryo; Zhang, Yingjie; Harrowfield, Jack; Kim, Yang; Hayami, Shinya; Nakamura, Masaaki
Abstract : A sextuply linked capsule incorporating two Ni(ii ) cubane units is formed when Ni(ii ) salts are reacted with N -aminoalkyl salicylamidato ligands in a 4 : 3 ratio in methanol. Abstract : A sextuply linked capsule incorporating two Ni(ii ) cubane units is formed when Ni(ii ) salts are reacted with N -aminoalkyl salicylamidato ligands in a 4 : 3 ratio in methanol. With a short (propyl) alkyl substituent, additional chloride counter ions are included in the cavity by occupation of one apex of each of the linked cubanes, while with a longer (pentyl) substituent, perchlorate and tetrafluoroborate anions are included, probably by H-bonding involving hydroxyl groups on the inner apices of the cubanes, indicating that the cavity can be regarded as suited to binding of hydrophilic units despite the lipophilic character of its links. The dicubane capsules show ferromagnetic behaviour typical of Ni(ii ) cubanes in general, with coupling constants dependent upon the nature of the salt-derived counter anions.